EDUKASI POSTUR TUBUH YANG BAIK DAN PEMBERIAN LATIHAN YANG DAPAT MENGURANGI NYERI PUNGGUNG BAWAH PADA PEKERJA HOUSEKEPEEPING DI ATLAS SPORT’S CLUB - Suwaibah, Suwaibah; Imanurrohmah Lubis, Zidni (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
Musculoskeletal disorders that often occur while working are low back pain. Low Back Pain (LBP) is pain felt in the lower back area, which can be local pain or radicular pain. Housekeeping itself is one of the jobs that has a high risk of experiencing Non-Specific LBP. This is due to a work posture that is prone to overloading the lower back. The work attitudes that are often used are bending, twisting, twisting, lifting or transporting goods. If this work attitude is carried out repetitively and for a long time, it can certainly increase the risk of Non-Specific LBP. This counseling method involves providing material pamphlets as well as pre-test and post-test questionnaires regarding understanding related to the material presented. The aim of holding this education is to increase knowledge and understanding regarding ergonomic body posture and how to treat lower back pain.